Avaliação da atividade antifúngica do geraniol sobre candida albicans e candida tropicalis isoladas de conteúdo pulmonar - Diniz Neto, Hermes (2018)
Recently, an increase in the number of hospital infections caused by Candida yeasts have been occurring, with a notable growing number of infections caused by non-albicans species, in addition to the already frequent cases caused by albicans species. The forms of superficial candidiasis may evolve to its systemic form, affecting different organs and being able to reach the lower airways, composing a condition of disseminated pulmonary candidiasis of complex diagnostic, difficult treatment and high mortality. As a way to obtain new therapeutic options in the combat against these infections, natural products of vegetal origin holds high scientific value due to their wide quantity of different substances of varied phytochemical classes. One of these classes, the monoterpenes, stands out for showing multiple biological activities of medical interest. Up to these premises, the antifungal activity of geraniol, a monoterpene, against strains of Candida albicans and Candida tropicalis was evaluated through in vitro assays: Determination of Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC), study of the substance effect on the fungal micromorphology, evaluation of the substance effect on the kinetics of microbial growth (time-kill) and association assay between geraniol and standard antifungal agent (amphotericin B). On the antifungal activity assays, the geraniol displayed MIC of 64 μg/mL and MFC of 256 μg/mL. The monoterpene also exhibited efficacy in inhibiting the appearance of virulence structures such as pseudohyphae and promote intense decrease of blastoconids in the micromorphology assay. On the time-kill assay, the monoterpene showed dose-dependent fungicide activity by inhibiting the growth of nearly 99% of the yeasts tested by the end of the 24 h period, with growth inhibition efficiency proportional to the concentration used. The association between geraniol and amphotericin B did not displayed synergism nor antagonism, being characterized as indifferent for not showing disparity between the association MIC and the substance’s isolated MIC. In conclusion, the monoterpene geraniol displayed important activity of fungicide character inhibiting the appearance of fungal virulence and resistance structures with efficacy depending directly on the concentration used, but without acting in synergism alongside the standard antifungal agent.